An Atom‐Economical Approach to 2‐Aryloxypyridines and 2, 2′/2, 3′‐Diaryloxybipyridines via Ruthenium‐Catalyzed [2+2+2] Cycloadditions. Issue 18 (30th July 2019) - Kalaramna, Pratibha; Bhatt, Divya; Sharma, Himanshu; Goswami, Avijit
Abstract: An efficient, ruthenium(II)‐catalyzed, solvent‐free approach for the synthesis of 2‐aryloxypyridines with good to excellent yields has been developed by the reaction of 1, 6‐diynes with aryl cyanates. This atom‐economical catalytic strategy offers a mild and practical approach to access a variety of such cycloadducts with excellent regioselectivities. The protocol was further extended to the synthesis of 2, 2′‐ and 2, 3′‐diaryloxybipyridines by the reaction of tetraynes with aryl cyanates. Abstract :